Gambaran Perawatan Anak Diare di Puskesmas Provinsi Bali - Nyoman Ribek; I Ketut Labir; Maria Dos Santos (Jurnal Gema Keperawatan, 2020)
The purpose of this study was to obtain a picture of the treatment of diarrhea performed in children in the Community Health Center. This study uses a qualitative research design with a case study approach. There were 8 participants in this study, namely 2 nurses who treated diarrhea children and 6 diarrhea children who were seeking care at the community health center. Participants were considered valid as informants because the 2 nurses already had experience in treating diarrhea while 6 diarrhea children were considered valid as informants at the time of participatory observation. Data from interviews, observations and documentation were analyzed according to miles and huberman including reduction, presentation and verification. It was concluded that to overcome the problem of readiness to improve fluid balance, hypovolemia and nutritional deficits in diarrhea patients given Paracetamol syrup 120 mg each 5ml, Neo Kaolana syrup 120 ml, zinc syrup and oralit. Paracetamol is given as a heat-lowering, Neo kaolana as a medicine for diarrhea, absorbs bacteria, toxins in the digestive tract and zinc also functions to treat diarrhea and oralit to relieve dehydration.